What factors affect the entrepreneurial intention to start-ups? The role of entrepreneurial skills, propensity to take risks, and innovativeness in open business models - Muhammad Farrukh Shahzad; Kanwal Iqbal Khan; Tayyiba Rashid (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Start-ups are launched every day, and most of them will fail at the same pace. Worldwide unemployment has become a major concern due to the geometric increase in the population. However, job opportunities are not created at the same pace as the overall population, and jobless people are becoming a burden on the economy. This situation led to introduce a system that helps people become self-employed and gives dignity to their lives. Prior studies reported that many factors could motivate an individual to pursue entrepreneurial projects. However, there is still a gap in identifying a path that promotes entrepreneurial intention among young graduates. Therefore, the purpose of the current study is to determine the effect of self-motivation, family support, peer influence, and institutional support on entrepreneurial intention through entrepreneurial skills, propensity to take risks, and innovativeness. Data were collected from 416 business students from six public and private sector universities in Pakistan. The results revealed that self-motivation, family support, peer influence, and institutional support positively and significantly affected entrepreneurial intention. The mediating role of entrepreneurial skills, a propensity to take risks, and innovativeness also enhances entrepreneurial intention among young graduates. A categorical analysis was conducted to explain the characteristics of the individuals motivated to launch start-ups. The results revealed a significant difference in the grouping variables of gender and education. The conceptual model provides more pronounced results in the case of male and post-graduate students. These findings may motivate young graduates to start new venture capital start-ups based on open business models. In this way, they can contribute to the complex and evolutionary economics that accelerate efficiency through technological innovation.
Keywords: 650; entrepreneurial intention; self-motivation; family support; peer influence; institutional support; entrepreneurial skills; propensity to take risks; innovativeness; open business models